Secagem do resíduo de acerola (Malphigia emarginata D.C.): estudo do processo e avaliação do impacto sobre o produto final - Nóbrega, Erly Maria Medeiros de Araújo (2012)
Brazil, one of the largest agricultural producers in the world, has managed in recent years to significantly improve its production. However, in response to this advance in the agro-industrial sector, the generation of agro-industrial residues has also increased. New technological alternatives have to be implemented in order to bring economic and rational use of this material and drying is one of the possible choices. Considering the great importance that bioactive compounds present for food science and technology, this research aims to evaluate the air-drying process of acerola residue in a tray convective drier under controlled temperature (60, 70 e 80ºC), air velocity (4.0, 5.0 e 6.0 m/s) and material width (0.5, 0.62 e 0.75 cm) by applying an experimental planning 23 + 3. Based on that, the impact on physical-chemical characteristics, color, bioactive compounds concentration and antioxidant activity of dried acerola waste was evaluated, having the in natura and freeze dried waste as control groups. Dried acerola residue presented natural pigments, mainly carotenoids (143.68 - 68.29 mg/g) and anthocyanins (290.92 - 90.11 mg/100 g), which explain the red and yellow instrumental color parameters observed. The acerola residue powder is also rich in phenolic compounds (3261.11 -2692.60 mgGAEeq/100g), proanthocyanidins (61.33-58.46 eq/100g), ascorbic acid (389.44 739.29 mg/100 g) and DPPH antioxidant activity (20.91 24.72 μg Trolox eq/g). Results show decreased concentration of phenolic compounds, anthocyanins, carotenoids, proanthocyanidins and ascorbic acid caused by the air-drying process. However, even after the observed drying losses, the acerola residue powder can be considered a high value food ingredient, considering the high bioactive compounds concentration found in the final product, as well as the colorimetric characterization and microbiological stability of the dried powder